2006
DOI: 10.1681/asn.2006030196
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inhibition of Mammalian Target of Rapamycin Signaling Downregulates Insulin Receptor Substrates 1 and 2 and AKT Activation

Abstract: Overactivation of the mammalian target of rapamycin (mTOR) branch downstream of the phosphatidylinositol 3-kinase-AKT pathway critically modulates insulin and growth factor signaling by insulin receptor substrates (IRS). On the basis of in vitro studies, the mTOR inhibitor rapamycin has been reported to lead to enhanced activation of AKT by relieving this feedback inhibition on IRS function. In view of the critical role of AKT in insulin signaling and tumorigenesis, the in vivo expression and activation of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 45 publications
8
68
0
Order By: Relevance
“…Moreover, it has been shown recently that chronic treatment with rapamycin disrupts mTORC2 complex and blocks its inhibiting activity on hepatic gluconeogenesis (69). Similar results were observed with a selective mTOR kinase inhibitor AZD8055, with an increase in blood glucose levels in treated mice (70). In humans, long-term treatment with rapamycin impaired insulin signaling assessed by the phosphorylation of Akt in circulating mononuclear cells (PBMC) of kidney-transplanted patients (71).…”
Section: Effects Of Mtor Inhibitors On Lipids "supporting
confidence: 56%
“…Moreover, it has been shown recently that chronic treatment with rapamycin disrupts mTORC2 complex and blocks its inhibiting activity on hepatic gluconeogenesis (69). Similar results were observed with a selective mTOR kinase inhibitor AZD8055, with an increase in blood glucose levels in treated mice (70). In humans, long-term treatment with rapamycin impaired insulin signaling assessed by the phosphorylation of Akt in circulating mononuclear cells (PBMC) of kidney-transplanted patients (71).…”
Section: Effects Of Mtor Inhibitors On Lipids "supporting
confidence: 56%
“…However, it is important to note that in vivo studies designed to reveal the importance of mTORC1 using rapamycin are less than ideal because of modulation of insulin sensitivity. 63,64 In addition, it is now accepted that a major limitation of rapamycin for in vivo and in vitro studies is the inhibition of mTORC1 activity toward only a subset of mTORC1 substrates. 8,9,[65][66][67] Therefore, inhibiting mTORC1 signaling in vivo by genetic deletion of Raptor in β cells will provide new insights into the role of this pathway in nutrient-and growth factor-dependent regulation of β-cell proliferation.…”
Section: How Downstream Mtorc1mentioning
confidence: 99%
“…Chronic administration of rapamycin has been associated with higher incidence of diabetes, although the relative contribution of β-cell dysfunction and insulin resistance to this effect is difficult to dissect. 63,64 It is possible that the alterations in insulin sensitivity could result from the signals from growth factors and nutrients, 69,[100][101][102][103][104][105] induces controlled growth and is rarely associated with malignancy. 106,107 The current evidence supports the concept that mTORC1 is active in states of increased insulin demand and plays a major role in β-cell expansion and proliferation induced by AKT and insulin resistance.…”
Section: How Decreased Akt Signaling By Mtorc1-mediated Negativementioning
confidence: 99%
“…Thus, long-term administration of everolimus may alter insulin secretion, as well as insulin-mediated peripheral glucose utilization and insulin-mediated suppression of hepatic glucose production (40), leading to hyperglycemia. In addition, insulin resistance may be worsened by ectopic triglyceride deposition (18).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Bourcier et al (11) reported the successful control of refractory hypoglycemia due to malignant insulinoma with the use of sirolimus, and a hyperglycemic effect with temsirolimus has been reported in patients treated for pNET and kidney cancer (12,13,14). To explain the occurrence of hyperglycemia in these patients, several hypotheses have been raised, including that a decrease in insulin production and release or an increase in peripheral insulin resistance may have been the cause (15,16,17,18,19). Kulke et al (20) first reported the symptomatic response of four patients treated with everolimus for uncontrolled hypoglycemia related to a metastatic insulinoma.…”
Section: Introductionmentioning
confidence: 99%